SIKAP DAN FAKTOR YANG MEMENGARUHI KONSUMEN DALAM PEMBELIAN BAKSO CURAH DI KOTA BANDAR LAMPUNG - Rahmat Sepriadi; Dyah Aring Hepiana Lestari; Maya Riantini (Lampung University, 2022)
This study aims to analyze the attitude of consumers and the factors that influence the purchase of meatballs bulk in Bandar Lampung. The markets which are analyzed in this research are Way Halim Market, Koga Market, and Gintung Market. The method that is used in this study is a survey method. Respondents in this study were selected randomly using the Accidental Sampling method. Respondents in this study were consumers of bulk beef meatballs that had bought bulk beef meatballs at least 3 times in the last 2 months. Types of data used in this study are primary data and secondary data. Before analyzing attitudes by Fishbein's multi-attribute analysis, the validity and reliability tests are first performed. To determine the factors that influenced the number of purchases of beef meatballs in bulk in Bandar Lampung City, multiple linear regression analysis is performed. Most respondents were housewives. The reaserch showed that attribute with the highest attitude score was the endurance attribute, while the cleanliness attribute, was the attribute with the smallest score. Factors that influence the number of consumers who bought meatballs in bulk were the price of bulk meatballs, the price of fish meatballs, the price of mustard greens, and the tastes of consumers. Fish meatballs were substitutes for bulk meatballs, if the price of bulk meatballs increases, consumers will choose to consume fish balls. Mustard was a complementary item from bulk meatballs, if the price of mustard greens increase, the purchase of bulk meatballs will decrease. Consumers who like the meatballs will tend to buy bulk meatballs with more amount than consumers who don’t like. Key words: attitude, consumers, decision, meatballs, purchasing